2010
DOI: 10.1074/jbc.m110.146704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trehalose on the Properties of Mutant γPKC, Which Causes Spinocerebellar Ataxia Type 14, in Neuronal Cell Lines and Cultured Purkinje Cells*

Abstract: Several missense mutations in the protein kinase C␥ (␥PKC) gene have been found to cause spinocerebellar ataxia type 14 (SCA14), an autosomal dominant neurodegenerative disease. We previously demonstrated that the mutant ␥PKC found in SCA14 is susceptible to aggregation, which induces apoptotic cell death. The disaccharide trehalose has been reported to inhibit aggregate formation and to alleviate symptoms in cellular and animal models of Huntington disease, Alzheimer disease, and prion disease. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Trehalose has peculiar physical-chemical properties that confer chaperone-like activities [42], such as the ability to stabilize mutant proteins [41,42,58]. Moreover, protein aggregates in neurodegenerative diseases are substrates of autophagy [21,36,59,60], a pathway that is enhanced by trehalose [3040].…”
Section: Discussionmentioning
confidence: 99%
“…Trehalose has peculiar physical-chemical properties that confer chaperone-like activities [42], such as the ability to stabilize mutant proteins [41,42,58]. Moreover, protein aggregates in neurodegenerative diseases are substrates of autophagy [21,36,59,60], a pathway that is enhanced by trehalose [3040].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compounds that are effective for the treatment of SCA14 could be available for the treatment of other neurodegenerative disorders. Because mutant γPKC-GFP rapidly induced aggregation and apoptosis within a few days in SH-SY5Y cells (31), this screening system could be beneficial for the exploration of novel candidates for therapeutics against SCA14, and these candidates might be effective for other neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that trehalose inhibits aggregation and apoptosis induction of mutant γPKC in SH-SY5Y cells and primary cultured PCs (31). Because the inhibition of apoptosis was not observed in PCs with preformed aggregates before trehalose treatment, this effect was mediated by the aggregation inhibitory property of trehalose.…”
Section: Exploration Of Novel Therapeutics Against Dysfunctions Triggmentioning
confidence: 94%
See 2 more Smart Citations